Sustainable Supply Chains in The Food Service Industry - Maria Vodenicharova; Lilyana Mihova (Universitas Pasundan, 2023)
This study aims to examine is to derive basic criteria and indicators for measuring the sustainability of the food supply chain, based on which to examine commercial food services in the food service industry and to derive guidelines for building a sustainable supply chain using innovative technologies. Based on the existing theoretical propositions, it has been further developed and applied in the food service industry sector. A survey was conducted in the period from March to May 2022 among 42 establishments in Bulgaria. The results аre developed food supply chain relationships in the commercial food service industry can increase back-and-forth supply chain resilience. Research, Practical & Social implications: The study establishes a need for necessary to introduce sustainability measures, through innovative technologies, with a view to bringing them into line with achievements, world trends, and the increased demands of users to provide ecofriendly services. This study reveals for the first time the food supply chain in the field of commercial food services in the food service industry and public catering in Bulgaria and provides guidelines for increasing sustainability.